Pengembangan Sistem Peringatan Dini menggunakan artificial intellegence Teknologi Sensor Menjaga Kesehatan Masyarakat dari Peningkatan Tingkat Bau di Pembuangan Sampah Akhir Cilowong Serang Banten: Pengabdian - Erwan Darmawan; Lani Febriani; Ghina Rizqandi Q.A; Muhamad Natsir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The increase in odor levels from the Cilowong Final Waste Disposal Site (TPSA), Serang, Banten, has had a negative impact on air quality and the health of the surrounding community. This community service activity aims to develop an early warning system based on Artificial Intelligence (AI). Artificial Intelligence (AI) and gas sensor technology to monitor in real time emissions of odorous gases such as hydrogen sulfide (H₂S), ammonia (NH₃), and volatile organic compounds (VOCs). This system is designed to analyze environmental data patterns using machine learning and provide early warnings to the public through a digital platform based on the Internet of Things (IoT). The development process refers to the CRISP-DM method in data processing and predictive modeling (Wirth & Hipp, 2000), and uses electrochemical-based sensors that have been proven effective in environmental monitoring (Kim et al., 2021). The implementation results show that the system is able to improve the community's rapid response to potential odor hazards and support decision-making by environmental managers. This innovation is a strategic step to encourage sustainable environmental management and protect public health from exposure to air pollutants.